OPINI AUDIT DAN PENGUNGKAPAN ATAS LAPORAN KEUANGAN PEMERINTAH KABUPATEN SERTA KAITANNYA DENGAN KORUPSI DI INDONESIA - Rini Rini; Adhariani Sarah (ETIKONOMI, 2014)
The study examined the relationship between the areas of financial reporting quality proxy by the audit opinion of the financial statements and the disclosure of local government (LKPD) districts, as well as the level of corruption in Indonesia. Study is qualitative and descriptive content analysis method (content) to process the data. The results of this study indicate that the quality of reporting of financial statements has increased as indicated by the improvement in the audit opinion above LKPD district in Indonesia. The second finding shows there is no link between the financial statement disclosures local government district with the opinion given by the BPK. The third findings showed case of corruption in Indonesian is increasing. The findings of the fourth, the disclosure of financial statements and audit opinions district has associated with the level of corruption in IndonesiaDOI: 10.15408/etk.v13i1.1875